2015
DOI: 10.4161/15384101.2014.991572
|View full text |Cite
|
Sign up to set email alerts
|

mTOR coordinates protein synthesis, mitochondrial activity and proliferation

Abstract: Protein synthesis is one of the most energy consuming processes in the cell. The mammalian/mechanistic target of rapamycin (mTOR) is a serine/threonine kinase that integrates a multitude of extracellular signals and intracellular cues to drive growth and proliferation. mTOR activity is altered in numerous pathological conditions, including metabolic syndrome and cancer. In addition to its well-established role in regulating mRNA translation, emerging studies indicate that mTOR modulates mitochondrial functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
412
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(429 citation statements)
references
References 108 publications
13
412
0
4
Order By: Relevance
“…PGC-1α, a transcriptional cofactor regulated by either AMPK or mTOR, is known to enhance mitochondrial biogenesis and oxidative phosphorylation (43,44). We found that combination of not only FCCP but also activators of mTOR and AMPK with PD-L1 mAb increased the expression levels of PGC-1α protein and mRNA in agreement with recent reports (Fig.…”
Section: Energy Sensors Ampk and Mtor Are Involved In Immune-enhancingsupporting
confidence: 82%
See 1 more Smart Citation
“…PGC-1α, a transcriptional cofactor regulated by either AMPK or mTOR, is known to enhance mitochondrial biogenesis and oxidative phosphorylation (43,44). We found that combination of not only FCCP but also activators of mTOR and AMPK with PD-L1 mAb increased the expression levels of PGC-1α protein and mRNA in agreement with recent reports (Fig.…”
Section: Energy Sensors Ampk and Mtor Are Involved In Immune-enhancingsupporting
confidence: 82%
“…We found that combination of not only FCCP but also activators of mTOR and AMPK with PD-L1 mAb increased the expression levels of PGC-1α protein and mRNA in agreement with recent reports (Fig. 6C) (35,43,44). The reduction of PGC-1α mRNA by PD-L1 mAb treatment alone despite an increase in its protein is probably due to multiple steps of PGC-1α regulation, namely transcription, translation, and protein stabilization (44,45).…”
Section: Energy Sensors Ampk and Mtor Are Involved In Immune-enhancingsupporting
confidence: 81%
“…mTORC1 is activated by multiple growth factors, insulin and nutrients through the PI3K/AKT pathway and has a central role in stimulating protein synthesis [63,64]. The interaction between eIF4G and eIF4E in the eIF4F complex is inhibited by 4E-binding proteins.…”
Section: Mtormentioning
confidence: 99%
“…The mTOR phosphorylation pathway directly governs the transcription of ERRalpha-target genes involved in energy metabolism including lipogenesis and citric acid cycle (71). Indeed, ATXN2 was found to modulate the leucine/mTORdriven phosphorylation of ribosomal protein S6 and also the incorporation rate of radioactive amino acids during mRNA Atxn2-KO Mice Have Impaired Nutrient Pathways translation (4).…”
Section: Atxn2-ko Mice Have Impaired Nutrient Pathwaysmentioning
confidence: 99%